The Gerasimov-Drell-Hearn sum rule and the spin structure of the proton - Krein, G. (Springer, 2001)
We present an overview of the present theoretical status of the Gerasimov-Drell-Hearn (GDH) sum rule. It is emphasized the importance of near threshold s- wave photoproduction contributions to the sum rule. We also discuss the experimental verification of the sum rule, with particular emphasis on the recent experiment at the Mainz Microtron (MAMI). The spin polarizabilities and the generalized GDH sum rule, which are of interest to issues related to the spin of the proton as measured at high energies, are discussed.